9H‐Quinolino[3, 2, 1‐k]phenothiazine: A New Electron‐Rich Fragment for Organic Electronics. Issue 50 (13th October 2016) - Poriel, Cyril; Rault‐Berthelot, Joëlle; Thiery, Sébastien; Quinton, Cassandre; Jeannin, Olivier; Biapo, Urelle; Tondelier, Denis; Geffroy, Bernard
Abstract: A new electron‐rich fragment, namely the quinolinophenothiazine (QPTZ) is reported. The QPTZ fragment incorporated in spiroconfigured materials leads to higher performance in blue Phosphorescent OLEDs than structurally related phenylacridine and indoloacridine based materials (increasing the HOMO energy level, modulating the spin‐orbit coupling, etc.) and leads to highly efficient blue phosphorescent organic light emitting diodes, indicating the strong potential of this new molecular fragment in organic electronics. Abstract : Organic semiconductors : A novel electron‐rich fragment for organic electronic applications, namely the quinolinophenothiazine (QPTZ), is reported. The sulfur atom of the QPTZ fragment plays a major role in the electronic properties (increasing the HOMO energy level, modulating the spin‐orbit coupling, etc.) and leads to highly efficient blue phosphorescent organic light emitting diodes, indicating the strong potential of this new molecular fragment in organic electronics (see scheme).